Development of Photo-Activated ROS-Responsive Nanoplatform as a Dual-Functional Drug Carrier in Combinational Chemo-Photodynamic Therapy - Chang, Yu-Cheng; del Valle, Andrea C.; Yeh, Huan-Pu; He, Yue; Huang, Yu-Fen (Frontiers in Chemistry, 2019)
Dual functional drug carrier has been a modern strategy in cancer therapy because it is a platform to elicit additive and synergistic effects through combination therapy. Photo-activated external stimuli such as reactive oxygen species (ROS) also ensure adequate drug delivery in a precise temporal and spatial manner. However, current ROS-responsive drug delivery systems usually require tedious synthetic procedures. A facile one-pot approach has been reported herein, to obtain self-assembled polymeric nanocarriers (NCs) for simultaneous paclitaxel (PTX)- and Rose Bengal (RB)-loading to achieve combined chemo-photodynamic therapy and controlled drug release in responsive to a light-induced ROS stimulus. To encapsulate these hydrophobic and hydrophilic drugs, chitosan (CTS), branched polyethylenimine (bPEI) and polyvinyl alcohol (PVA) were selected and fabricated into nanoblended matrices through an oil-in-water emulsion method. The amphiphilic properties of CTS permit simultaneous entrapment of PTX and RB, while the encapsulation efficiency of RB was further improved by increasing the amount of short-chain bPEI. During the one-step assembly process, bovine serum albumin (BSA) was also added to condense the cationic tripolymer mixtures into more stable nanocarriers (BNCs). Hyaluronic acid (HA) was subsequently grafted onto the surface of BNCs through electrostatic interaction, leading to the formation of HA-BSA/CTS/PVA/bPEI-blended nanocarriers (HBNCs) to achieve an efficient prostate-cancer-cell uptake. Importantly, in response to external light irradiation, HBNCs become destabilized owing to the RB-mediated photodynamic action. It allows an on-demand dual-payload release to evoke a simultaneous photodynamic and chemo treatment for cancer cell eradication. Thus, HBNCs present a new promising approach that exhibits a specific vulnerability to RB-induced photosensitization. The consequent dual-cargo release is also expected to successfully combat cancer through a synergistic anti-tumor effect.